Liquidity, Uncertainty, and the Declining Predictive Power of the Paper-bill Spread - J. Peter Ferderer; Stephen C. Vogt; Ravi Chahil (Levy Economics Institute of Bard College, 1994)
This paper addresses two questions. First, what causes the paper-bill spread to vary over time in anticipation of income fluctuations ? Second, why has the predictive power of the spread declined in recent years? Consistent with previous empirical work, the paper provides evidence for the default-risk, monetary, and cash-flow hypotheses. Moreover, new evidence is provided for the liquidity hypothesis by showing that uncertainty has a strong impact on the paper-bill spread. This finding holds for two different approaches used to measure uncertainty - financial market volatility and forecaster discord - and for uncertainty about five different variables: the federal funds rate, the Treasury bill rate, the long-term corporate bond rate, stock returns, and industrial production. Using a Kalman filter to recursively estimate the reduced-form model for the paper-bill spread, the paper shows that the impact of monetary policy and uncertainty on the spread declined during the 1980s, while the impact of default risk increased. These findings are explained by two financial market developments occurring during the 1980s: 1) the rapid growth in the volume and liquidity of the commercial paper market, and 2) increased financial fragility of commercial paper issuers.
Keywords: E32; E44; 330